New Enzymatic Targets for Organophosphorus Compounds - E. N. Efremenko; A. G. Aslanli; I. V. Lyagin (Вестник войск РХБ защиты, 2023)
It is known that several decarboxylases (aromatic amino acid decarboxylase (AAD), histidine decarboxylase (HD) and glutamate decarboxylase (GD) with different molecular weights catalyze the most important reactions of neurotransmitter and neuromodulator biosynthesis. Pyridoxal phosphate, which serves as a cofactor for these enzymes, is one of organophosphorus compounds (OPC) having a structure similar to highly toxic substances such as warfare agents (WA) sarin, soman, Vx, a substance of type Vx, tabun and the so-called «Novichoks» (A230, A232, A234), as well as pesticides, widely used in agriculture (chlorpyrifos, malathion, glyphosate, mipafox, diazinon, paraoxon), based on their inhibitory effect on cholinesterases (ChE). The purpose of this work was to use computer modeling methods to evaluate the possible binding of various OPC to the catalytic centers of these enzymes instead of a cofactor, as well as similar interactions of decarboxylases (DC) with OPC when the active centers of DC already contain a built-in cofactor. Molecular docking has shown that a number of these OPC can compete with the cofactor for binding to the active centers of DC, and absolutely all the studied OPC (pesticides and WA) create obstacles to embedding the cofactor in the active center of AAD and HD. Such interactions will lead to a decrease in the level of formation of products of the corresponding catalytic reactions (dopamine, serotonin, phenylethylamine, serotonin, γ-aminobutyric acid) and the manifestation of their physiological functions. It was found that in the presence of a cofactor in the active center of the studied DC, the interaction of a number of OPC with the surface of these enzymes near the active center increases and exceeds the strength of the interaction of same enzymes with their typical substrates. At the same time, the maximum interaction that can lead to a significant inactivation of all the studied DC was revealed for the pesticides, while the effect of their presence was lower for WA. One of the highest levels of possible influence on the activity of DC was revealed for chlorpyrifos and diazinon. In total, for DC, the more dangerous substances with high potential neurotoxicity turned out to be not WA at all, including «Novichoks», namely pesticides, which, according to their known effect on ChE, are considered as low-toxic OPC. The conducted new theoretical studies indicate that, firstly, direct experimental studies are required that will confirm the bioinformatics calculations made; secondly, a revision of long-standing approaches to assessing the neurotoxicity of various OPC, based mainly on the use of ChE for these purposes, is necessary; thirdly, it may be necessary to formulate tasks for the development and the use of new systems for the determination of potentially neurotoxic substances, the effect of which will be based on the use of different DC; fourth, to study the possible using DC as a basis for the development of new catalytic enzymatic detoxifiers (antidotes) and CNS regenerators.